Gut microbiota-derived indole 3-propionic acid partially activates aryl hydrocarbon receptor to promote macrophage phagocytosis and attenuate septic injury - Huang, Zhi-Bin; Hu, Zhen; Lu, Chen-Xin; Luo, Si-Dan; Chen, Yu; Zhou, Zhi-Peng; Hu, Jing-Juan; Zhang, Fang-Ling; Deng, Fan; Liu, Ke-Xuan (Frontiers in Cellular and Infection Microbiology, 2022)
Sepsis is associated with a high risk of death, and the crosstalk between gut microbiota and sepsis is gradually revealed. Indole 3-propionic acid (IPA) is a gut microbiota-derived metabolite that exerts immune regulation and organ protective effects. However, the role of IPA in sepsis is not clear. In this study, the role of IPA in sepsis-related survival, clinical scores, bacterial burden, and organ injury was assessed in a murine model of cecal ligation and puncture-induced polymicrobial sepsis. Aryl hydrocarbon receptor (AhR) highly specific inhibitor (CH223191) was used to observe the role of AhR in the protection of IPA against sepsis. The effects of IPA on bacterial phagocytosis by macrophages were investigated in vivo and vitro. The levels of IPA in feces were measured and analyzed in human sepsis patients and patient controls. First, we found that gut microbiota-derived IPA was associated with the survival of septic mice. Then, in animal model, IPA administration protected against sepsis-related mortality and alleviated sepsis-induced bacterial burden and organ injury, which was blunted by AhR inhibitor. Next, in vivo and vitro, IPA enhanced the macrophage phagocytosis through AhR. Depletion of macrophages reversed the protective effects of IPA on sepsis. Finally, on the day of ICU admission (day 0), septic patients had significantly lower IPA level in feces than patient controls. Also, septic patients with bacteremia had significantly lower IPA levels in feces compared with those with non-bacteremia. Furthermore, in septic patients, reduced IPA was associated with worse clinical outcomes, and IPA in feces had similar prediction ability of 28-day mortality with SOFA score, and increased the predictive ability of SOFA score. These findings indicate that gut microbiota-derived IPA can protect against sepsis through host control of infection by promoting macrophages phagocytosis and suggest that IPA may be a new strategy for sepsis treatment.